Here comes the rain - Murphy, Mary, 1961- (New York : Dorling Kindersley, 2000)
A cat tries to run away from a rain cloud, but when the rain comes she finds that it is cool, tickly, gentle, clean, and lovely.
Keywords: Rain and rainfall -- Fiction; Cats -- Fiction